CRISIS-RESPONSIVE SOCIAL PROTECTION: COUNTERFACTUAL EVIDENCE ON POVERTY REDUCTION FROM INDONESIA'S RESPONSE TO COVID-19 - Haryaningsih, Sri; Andriani, Farah Devi; Pambudi, Argo; Seran, Silverius Tey; Sihaloho, Nahot Tua Parlindungan (Universitas Negeri Yogyakarta, 2024)
This article assesses the crisis-response performance of Indonesia's social protection in reducing poverty amidst the COVID-19 pandemic. Based on a quasi-experiment framework and counterfactual method, we take advantage of the staggered rollout and varying intensity of emergency assistance to infer poverty results under a counterfactual situation of no program intervention. Based on nationally representative household surveys matched with administrative records, our estimates indicate that the swift growth of cash and food assistance programs saved the country from an extra four percentage point rise in the national poverty rate, thereby keeping nearly 11 million individuals from descending into poverty. The effects were the largest for the poorest families, where social assistance accounted for as much as 22 percent of expenditures on a monthly basis. Robustness checks using other poverty lines and placebo tests validate the robustness of these findings. Yet, targeting accuracy and coverage of informal sector workers remain concerns. The findings underscore the essential importance of administrative preparedness and unified data systems for an effective crisis response, and provide policy implications for enhancing the resilience of social protection institutions in developing nations.